Critical evaluation of fracture strength testing for endodontically treated teeth: a finite element analysis study - Emel Uzunoglu-Özyürek; Selen Küçükkaya Eren; Oğuz Eraslan; Sema Belli (Restorative Dentistry & Endodontics)
ObjectivesThe aim of this study was to investigate whether the diameter and direction of the plunger and simulation of the periodontal ligament (PDL) affected the stress distribution in endodontically treated premolars.MethodsA fracture strength test was simulated via finite element analysis. A base model was set up, and the following parameters were modified: plunger diameter (3 mm vs. 6 mm), plunger direction (vertical vs. 135° angular to the central fossa), and PDL simulation. The analysis was conducted using the CosmosWorks structural analysis program, and the results are presented in terms of von Mises stresses.ResultsThe smaller plunger increased the stresses at the contact area of the crown, but the plunger diameter had no effect on the stress distribution within the root. An angular plunger direction increased stresses within the root, as well as at the buccal cusp of the crown, compared with the vertical direction. Simulation of the PDL caused higher stress accumulation, especially in the cervical region of the root.ConclusionsThe plunger diameter had no effect on the stress distribution in the roots, whereas the plunger direction and PDL simulation did affect the stress distribution. More stringent standards can be established by taking such parameters into account when performing fracture testing in future studies.